DINAMIKA KEBIJAKAN PENDIDIKAN AGAMA ISLAM DI PERGURUAN TINGGI UMUM - Hamka Hamka (Scolae: Journal of Pedagogy, 2018)
This article examines the Indonesian Government's policy on the implementation of Religious Education at Public Higher Education. The research is conducted through a socio-cultural-historical approach using content analysis methods to relevant texts, both in book form and related documents. The results show that the policy of Islamic Religious Education in public universities is influenced by the assumption and response of policy maker, in this case the government (Old Order, New Order and Reform Order), to the socio-political and cultural reality that developed in society, this is in accordance with K. Young's theory. The policy is part of the government's effort to control the implementation of Islamic Religious Education in public universities, as described in Roger Dale's theory, through regulation, bureaucratic system, the implementation of obligations and political reproduction in the Indonesian context.